Problematika Publisistik Mushaf Al Quran Di Indonesia - Eka Sari Yanti; Rasyidah (Sadida Islamic Communications and Media Studies, 2023)
This research was conducted to look at the history of printing the Al-Qur'an. Apart from being a source of civilization, efforts to study the history of the printing of the Koran continue to be carried out, because the Al-Quran is a book that is continuously read and guided by all Muslims. This research uses literature review by examining various references related to the history of printing the Al-Quran from the time of the Prophet to the present. The benefit of this research is that it provides readers with an understanding of the history of Al-Qur'an printing and its problems. The results of this research show that the printing of the Al-Quran in Indonesia often occurs in terms of writing, finishing techniques, publication ethics, lack of standard references and inappropriate use of Al-Quran paper waste among the public. The background to the causes of these errors is generally due to a lack of regulation from the government which has a deterrent effect on publishers and printers, as well as a lack of government outreach regarding the publication and printing of the Al-Quran and a lack of waste management according to procedures.